Exploring a tumor spectrum in a patient with familial angiolipomatosis - Maheshwari, Shradha; Arora, Eham (Asian Journal of Neurosurgery, 2019)
Angiolipomas are uncommon spinal tumors which differ from their cutaneous counterparts in having larger caliber vascular stroma. Although slow growing, they can cause rapid spinal cord compression and sudden-onset sensorimotor symptoms due to vascular engorgement, hemorrhage, or thrombosis. The goal of surgery is spinal decompression, and favorable outcome is the rule. We report a patient with spinal angiolipoma, vertebral hemangioma along with subcutaneous lipomas and angiolipomas, exhibiting the entire histopathological spectrum of these related soft-tissue tumors. Analysis of his family tree revealed a hereditary predilection. Familial angiolipomatosis is an uncommon genetic condition which has not been reported to occur with spinal angiolipomas thus far.
Keywords: Angiolipoma; familial angiolipomatosis; spinal angiolipoma